ANALISIS PENGARUH STRATEGI OFFLINE TO ONLINE (O2O) TERHADAP PENJUALAN UMKM MITRA APLIKASI BADOKANGRESIK.ID - Alfista Firdaus; Raya Sulistyowati (Niagawan, 2021)
Business strategies that MSMEs can implement in the digitization era is the Offline to Online (O2O) strategy. This study aims to analyze the influence of Offline to Online (O2O) strategy on the MSMEs sales of BadokanGresik.id application partners. This research is descriptive quantitative research. The sampling techniqueused is random sampling where the sample used is 62 MSME partners in the BadokanGresik.id application. The data collection technique used a questionnaire distributed with the help of Google Form. The hypothesis was tested using simple linear regression analysis processed with SPSS 25, including t test, coefficient of setermination test and F test. The results of data analysis showed that partially, Offline to Online (O2O) strategy has a significant and positive effect on sales. Simultaneously, the Offline to Online (O2O) strategy has positively and significantly influence ales of MSMEs.